2004
DOI: 10.1038/sj.onc.1207422
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP kinase signaling is necessary for rat chondrosarcoma cell proliferation

Abstract: Chondrosarcomas represent the second most frequent class of primary skeletal malignancies. This tumor type is highly resistant to radiation therapy and currently available chemotherapies, thereby limiting treatment choice to surgical resection. Identifying the mechanisms responsible for chondrosarcoma cell proliferation is therefore crucial for the development of new treatment strategies. Here, we demonstrate a significant reduction in rat chondrosarcoma cell proliferation following treatment with pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Immunoprecipitated (IP) Cdk2 activity was measured in a kinase assay using histone H1 as a substrate and [g- airway smooth muscle cells stimulated by fibroblast growth factor-2 (22, 23), of hematopoietic cells stimulated by cytokines (24,25), and of vascular smooth muscle and pancreatic stellate cells stimulated by platelet-derived growth factor (26,27). p38 MAPKs are also required for CD40-induced proliferation of B-lymphocytes (28), and for cell cycle progression of breast cancer, melanoma and chondrosarcoma cell lines (29)(30)(31). However, the signaling pathways and identities of signaling key intermediates, which mediate p38 MAPK involvement in cell cycle progression, are poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitated (IP) Cdk2 activity was measured in a kinase assay using histone H1 as a substrate and [g- airway smooth muscle cells stimulated by fibroblast growth factor-2 (22, 23), of hematopoietic cells stimulated by cytokines (24,25), and of vascular smooth muscle and pancreatic stellate cells stimulated by platelet-derived growth factor (26,27). p38 MAPKs are also required for CD40-induced proliferation of B-lymphocytes (28), and for cell cycle progression of breast cancer, melanoma and chondrosarcoma cell lines (29)(30)(31). However, the signaling pathways and identities of signaling key intermediates, which mediate p38 MAPK involvement in cell cycle progression, are poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…20 l of lysate were used to determine relative luciferase activity (firefly luciferase activity divided by Renilla luciferase activity) using a dual luciferase assay system (Promega). Data analyses were done as described previously (47).…”
Section: Methodsmentioning
confidence: 99%
“…A number of in vitro studies have suggested that p38 potentially regulates chondrocyte proliferation. However, both proliferative and antiproliferative effects have been reported based on the effects of p38 inhibitors in a number of culture systems (18,21,25,26). Therefore, examining how increased or decreased p38 activity in chondrocytes affects chondrocyte differentiation, proliferation, and the entire process of endochondral ossification in intact animals is of considerable interest.…”
mentioning
confidence: 99%
“…Indeed, we recently showed that constitutive activation of the MEK1-MAPK pathway in chondrocytes in transgenic mice inhibits hypertrophic chondrocyte differentiation and causes a dwarf phenotype without a decrease in cell proliferation (16). The p38 MAPK pathway, another subfamily of the MAPK pathways, has also been shown to affect chondrocyte differentiation in chondrocyte cultures (17)(18)(19)(20)(21)(22)(23). p38 MAPKs consist of four isoforms, all of which are activated by MKK6, an upstream MAPKK (24).…”
mentioning
confidence: 99%